PERSEPSI SISWA TERHADAP PEMANFAATAN E-BOOK SIBI SEBAGAI SARANA LITERASI DIGITAL DALAM PEMBELAJARAN BAHASA INDONESIA - Maratussholihah, Zuhrotul; Ahmadi, Anas; Raharjo , Resdianto Permata (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2024)
This research aims to identify students' perceptions of the use of SIBI e-books which are used as a means of digital literacy in learning Indonesian. The method used in this research is a survey method with a quantitative approach. The research sample used was students of class XI F4 SMA Negeri 1 Mantup using a purposive sampling technique. Data collection in this research used a questionnaire technique with a questionnaire sheet as the instrument. The data analysis used in this research is descriptive statistics to determine the mean and percentage of student questionnaire results. The results of data analysis show that the perception of class These results indicate that student perceptions lead to positive perceptions. Students and teachers can receive and utilize SIBI e-books very well as a means of digital literacy and support in learning Indonesian. SIBI e-books are digital media that are very relevant, good, and effective in developing students' digital literacy, especially in learning Indonesian.